PROFESIONALISME GURU DALAM DUNIA PENDIDIKAN PROSES BELAJAR MENGAJAR BERBASIS PENDIDIKAN KARAKTER DI MASA PANDEMI COVID-19 - Luh De Liska (Jurnal Ilmiah Cakrawarti, 2021)
Professional teachers are responsible for fostering, guiding, educating, assessing and evaluating their students to be able to have quality character education. A teacher must also be able to adapt himself openly, wisely and be able to respond well to the entry of the globalization era in today's era. Especially during the Covid-19 pandemic, it becomes a challenge for a teacher, considering the factors that affect character education are 1) the increasingly rapid flow of globalization, 2) the crisis of an identity, moral and social of a nation. The purpose of this research is to apply a strategic way in making a generation of a nation that has quality character education. The method used is library research. The results of this research are expected later, the professionalism of a teacher in the teaching and learning process can make quality character education for students, especially during this Covid-19 pandemic.